2015
DOI: 10.22495/cocv13i1c9p9
|View full text |Cite
|
Sign up to set email alerts
|

The value relevance of voluntary intellectual capital disclosure: New Zealand evidence

Abstract: The purpose of this study is to investigate the value relevance of voluntary intellectual capital disclosure (ICD) in New Zealand by examining the relationship between voluntary ICD and market value. The results suggest that the relationship between voluntary ICD and market value is not a simple, positive relationship across the board. That is, the benefits of different types of intellectual capital (IC) - namely human, relational and structural capital - may vary significantly, and there may even be some cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
2
8
0
1
Order By: Relevance
“…Vafaei et al (2011) confirmed this result by analysing a sample of companies traded on the British, Australian, Hong Kong and Singapore stock markets. Similar results were obtained by Gamerschlag (2013) in Germany, as well as Ellis and Seng (2015) in New Zealand. Considering stocks listed on the ASX, Dumay and Tull (2007) observed that the diffusion of IC-related information in price-sensitive announcements had an impact on subsequent cumulative abnormal returns.…”
Section: Literature Reviewsupporting
confidence: 87%
See 1 more Smart Citation
“…Vafaei et al (2011) confirmed this result by analysing a sample of companies traded on the British, Australian, Hong Kong and Singapore stock markets. Similar results were obtained by Gamerschlag (2013) in Germany, as well as Ellis and Seng (2015) in New Zealand. Considering stocks listed on the ASX, Dumay and Tull (2007) observed that the diffusion of IC-related information in price-sensitive announcements had an impact on subsequent cumulative abnormal returns.…”
Section: Literature Reviewsupporting
confidence: 87%
“…As a productive factor, IC is fundamental in knowledge-based industries (Hansson, 1997; Ellis and Seng, 2015). Thus, the assumptions used to build this study’s equilibrium model are more likely to occur in the pharmaceutical industry, where IC plays a key role in successfully developing new drugs and obtaining approval from regulatory authorities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of empirical studies in different countries that focus on the relationship between IC information and market value. For example, in the USA (Abdolmohammadi, 2005), Britain, Australia, Hong Kong, Singapore (Vafaei et al , 2011), Sri Lanka (Abeysekera, 2011), Malaysia (Ousama et al , 2011b; Taliyang et al , 2014), German (Gamerschlag, 2013), New Zealand (Ellis and Seng, 2015), ASEAN countries (Nimtrakoon, 2015), Pakistan (Dashti et al , 2016) and Kuwait (Alfraih, 2017). These studies found a positive significant relationship between IC information and market value, consequently providing empirical evidence on the value relevance of IC information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such studies deal with the intangible resources and their financial impact on the firm's value, trying to incorporate the qualitative view focused on intangibles strategy into a quantitative framework to measure the accounting value relevance. In some case studies, the value relevance of voluntary intellectual capital disclosure (rather than mandatory accounting) has been investigated by examining the impact on market value (Ellis & Seng, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%